2021
DOI: 10.21608/atasu.2021.170161
|View full text |Cite
|
Sign up to set email alerts
|

Are Tax Avoidance, Corporate Social Responsibility and Financial Performance Affecting Firm Value in the Egyptian Listed Companies?

Abstract: Although previous studies have examined the relationship between tax avoidance and corporate social responsibility, there is no evidence for this relationship in emerging economies, including Egypt that characterized by a weak institutional, enforcement systems and investor protection and a high level of corruption. Therefore, this research examines the relationship between tax avoidance and the level of corporate social responsibility disclosure and show how both have an impact on the firm value.The topic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Board characteristics play a crucial role in influencing ESG disclosure practices. Research has shown that board diversity, including gender diversity, is positively associated with ESG disclosure (Manita et al, 2018;Masi et al, 2021;Nicolò et al, 2021;Wasiuzzaman & Subramaniam, 2023) According to legitimacy theory, firms with poor sustainability performance may strategically use additional sustainability disclosures to influence the perception of market participants and maintain their legitimacy (Abd-Elmageed, 2021;Kumawat & Patel, 2022). This aligns with the notion that organizations engage in ESG disclosure to mitigate concerns and maintain their legitimacy (Abd-Elmageed, 2021).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Board characteristics play a crucial role in influencing ESG disclosure practices. Research has shown that board diversity, including gender diversity, is positively associated with ESG disclosure (Manita et al, 2018;Masi et al, 2021;Nicolò et al, 2021;Wasiuzzaman & Subramaniam, 2023) According to legitimacy theory, firms with poor sustainability performance may strategically use additional sustainability disclosures to influence the perception of market participants and maintain their legitimacy (Abd-Elmageed, 2021;Kumawat & Patel, 2022). This aligns with the notion that organizations engage in ESG disclosure to mitigate concerns and maintain their legitimacy (Abd-Elmageed, 2021).…”
Section: Literature Reviewmentioning
confidence: 91%
“…In addition, Abdullah (2020) found that there is a positive association between CSR and tax avoidance, and firms headquartered in low financial-tax reporting conformity jurisdictions are more likely to engage in CSR to hedge against the potential negative consequences of aggressive tax-avoidance practices as compared to firms domiciled in countries with high level of financial-tax reporting conformity. Abd-Elmageed and Abo Ashour (2021) found that that companies involved in tax avoidance strategies are likely to increase CSR disclosures. These results are consistent with the legitimacy theory that companies increase ESG disclosures to alleviate community concerns about lower tax payments and build legitimacy.…”
Section: The Moderating Effect Of Women Directorsmentioning
confidence: 99%
“…These results are consistent with the statistics presented by Shafer and Simmons (2008) and confirm that CSR practices are positively related to ethical and socially responsible judgements of tax evasion and negatively related to the behavioural intentions of this practice. Abd-Elmageed and Abo Ashour (2021) also demonstrated that whilst corporate tax policy is generally considered separate from CSR policy, tax evasion has a significant impact on the social agenda worldwide, especially during the global financial crisis (Duhigg and Kocieniewski, 2012). Thus, socially responsible companies practice less tax evasion because they view the company as a “real world” entity where CSR is a legitimate business activity and not just a cost on the way to shareholder wealth maximisation (Hessaldine and Morris, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Given that most global tax revenue losses come from developing countries (Elouadi and Ben Noemene, 2015; Abd-Elmageed and Abo Ashour, 2021) and that taxes are the principal source of revenue in the majority of these countries, it is essential to contribute to the literature in this area. The conceptual framework proposed by Cobham and Janský (2018) is critical to the broader literature aimed at understanding corporate tax behaviour, particularly how firms view tax evasion from an ethical perspective.…”
Section: Introductionmentioning
confidence: 99%